The Effect of Carbohydrate Diet Program on Urine Ketone Positivity with A Long Time on A Diet of One until Three Years - Maya, Kadek; Pauzi, Iswari; Zaetun, Siti (Balai Publikasi Indonesia, 2024)
Carbohydrate diet is a diet pattern that reduces carbohydrate consumption. Therefore, the body will use fat as an alternative energy source. The continuous use of fat causes the accumulation of fatty acids so it is often the cause of ketone positivity in the urine. Objective: Find out the effect of a carbohydrate diet program on the positivity of urine ketones. Method this research is an analytic observational study with a cross-sectional approach. The sample used was urine from respondents who had been on a carbohydrate diet for 1 year, 2 years, and 3 years, then urine ketones were examined using the dipstick method. Data analysis was carried out using the Chi-Square test with a confidence value (α = 0.05). Result: The sample in this study amounted to 45 samples, with a total of 23 samples of positive ketones and 22 samples of negative ketones. The results of the Chi-Square test obtained an Asymp.sig value of 0.009 <0.05 (α) which indicates that the carbohydrate diet program has a significant effect on the positivity of urine ketones. The carbohydrate diet program affects urine ketone levels.